Lurkers in social networks - Rabiah Raihan (2016)
Lurkers in social networks are silent members in a social network who play passive roles and contribute very little in the network. The so-called lurkers make up close to 90% of the online social network users. This huge number of inactive users created an awareness to research in which is worth the exploration. Many lurking-related researches had been done under the category of social science, cognitive psychology and computer-human interaction. There had only been one study of this lurking phenomenon that is categorised as data mining and information retrieval. This project investigates the study of lurking phenomenon based on data mining in turn ranking the lurkers with different ranking methods such as Page Rank and Alpha-Centrality. This report records the investigation and derivation of all the definitions used to formulate the topology driven concept into the LurkerRank methods through programming and testing algorithm in MATLAB.